Apprendere (con) l’intelligenza artificiale. Un approccio media-archeologico - Stefano Moriggi; Mario Pireddu (Journal of Educational, Cultural and Psychological Studies)
LEARNING (WITH) ARTIFICIAL INTELLIGENCE. A MEDIA-ARCHAEOLOGICAL APPROACH